Zero sequence power line current measurement by using magnetic field sensor array. (24th April 2014) - Lin, Shunfu; Gao, Pengfei; Xu, Wilsun
Summary: Knowledge of the zero sequence current (ZSC) in an overhead power line is very important for troubleshooting grounding‐related power quality problems. Unfortunately, no simple and easy‐to‐use method for measuring the ZSC is available. This article presents a simple, portable, and non‐contact ZSC measurement method based on the concept of the magnetic field sensor array. This innovative method uses magnetic field sensors located on the ground, vertically below an overhead power line. The ZSC is calculated by using the measured magnetic fields associated with the power line currents. The proposed method is a non‐contact and power disturbance‐free device. Its theory and basic operation principle are presented. The results of the simulation studies carried out for evaluation are reported. A laboratory set‐up was developed accordingly, and extensive experimental results confirmed the feasibility and validity of the proposed method. Copyright © 2014 John Wiley & Sons, Ltd.